2004
DOI: 10.1155/s1110724304403131
|View full text |Cite
|
Sign up to set email alerts
|

Retrotransposition‐Competent Human LINE‐1 Induces Apoptosis in Cancer Cells With Intact p53

Abstract: Retrotransposition of human LINE-1 (L1) element, a major representative non-LTR retrotransposon in the human genome, is known to be a source of insertional mutagenesis. However, nothing is known about effects of L1 retrotransposition on cell growth and differentiation. To investigate the potential for such biological effects and the impact that human L1 retrotransposition has upon cancer cell growth, we examined a panel of human L1 transformed cell lines following a complete retrotransposition process. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 40 publications
2
60
0
1
Order By: Relevance
“…This work goes on to suggest that this diminished retrotransposition is the result of Bax-induced apoptosis (Haoudi et al, 2004). Indeed, it has also been shown that L1 expression can induce apoptosis in MCF7 cells, a cell line with wild type p53 (Gasior et al, 2006a;Shiloh 2003;Haoudi et al, 2004).…”
Section: L1 Expression and Toxicity In Mcf7 And Hela Cellsmentioning
confidence: 94%
See 3 more Smart Citations
“…This work goes on to suggest that this diminished retrotransposition is the result of Bax-induced apoptosis (Haoudi et al, 2004). Indeed, it has also been shown that L1 expression can induce apoptosis in MCF7 cells, a cell line with wild type p53 (Gasior et al, 2006a;Shiloh 2003;Haoudi et al, 2004).…”
Section: L1 Expression and Toxicity In Mcf7 And Hela Cellsmentioning
confidence: 94%
“…This work goes on to suggest that this diminished retrotransposition is the result of Bax-induced apoptosis (Haoudi et al, 2004). Indeed, it has also been shown that L1 expression can induce apoptosis in MCF7 cells, a cell line with wild type p53 (Gasior et al, 2006a;Shiloh 2003;Haoudi et al, 2004). As expected, we observe very little retrotransposition when a tagged L1 retrotransposition cassette is transfected into MCF7 cells, despite relatively high transfection and colony-forming efficiencies as measured by parallel transfection of a hygromycin resistance cassette ( Figure 1B).…”
Section: L1 Expression and Toxicity In Mcf7 And Hela Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Infection by retroviruses can lead to induction of apoptosis [66,67], and HIV Nef activates caspases [66], the targets of IAP proteins. Waves of intracellular retrotransposition can also be associated with increased apoptosis [68]. Therefore, retroviral/retroelement insertions in germ line cells which, by chance, induce expression of anti-apoptotic genes, could abort an initial or transitory stress-induced apoptotic response, increasing the probability that cells harboring such insertions would survive and contribute to subsequent generations, assuming they have not suffered damage.…”
Section: Discussionmentioning
confidence: 99%